Attachment of class B CpG ODN onto DOTAP/DC-chol liposome in nasal vaccine formulations augments antigen-specific immune responses in mice. (December 2017) - Tada, Rui; Muto, Shoko; Iwata, Tomoko; Hidaka, Akira; Kiyono, Hiroshi; Kunisawa, Jun; Aramaki, Yukihiko
Abstract Background To overcome infectious diseases, the development of mucosal vaccines would be an effective strategy, since mucosal surfaces are the entry site for most pathogens. In general, protein antigens show inherently poor immunogenicity when administered by the mucosal route. Therefore, co-administration of an appropriate mucosal adjuvant is required to exert immune responses toward pathogen-derived antigens effectively. However, the development of a safe and effective mucosal adjuvant system is still challenging. Although, recent studies reported that oligodeoxynucleotides (ODNs) containing immunostimulatory CpG motifs (CpG ODNs) act as potent mucosal adjuvants and are useful in the formulation of nasal vaccines, there are some disadvantages. For instance, the administration of phosphorothioate (PS)-modified CpG ODNs can induce adverse systemic effects, such as splenomegaly, in a dose-dependent manner. Therefore, a reduced dose of CpG ODN might be crucial when used as vaccine adjuvant for clinical purposes. Therefore, we prepared a CpG ODN-loaded cationic liposome, and evaluated its mucosal adjuvant activity. Results We prepared a CpG ODN-loaded DOTAP/DC-chol liposome that was stable during our experiments, by mixing CpG ODNs and liposomes at an N/P ratio of 4. Further, we demonstrated that the attachment of class B CpG ODN to the DOTAP/DC-chol liposomes synergistically enhanced antigen-specific IgA production in the nasal area than that induced by CpG ODN and DOTAP/DC-chol liposomes alone. The endpoint titers were more than tenfolds higher than that induced by either single CpG ODN or single DOTAP/DC-chol liposomes. Additionally, although serum IgG1 responses (indicated as a Th2 response) remained unchanged for DOTAP/DC-chol liposomes and CpG ODN-loaded DOTAP/DC-chol liposomes, the CpG ODN-loaded DOTAP/DC-chol liposomes synergistically induced the production of serum IgG2a (indicated as a Th1 response) than that by the individual liposomes. Conclusions We conclude that the advantage of using DOTAP/DC-chol liposome harboring CpG ODN is it induces both antigen-specific mucosal IgA responses and balanced Th1/Th2 responses. Therefore, such a combination enables us to resolve the adverse effects of using CpG ODNs (as a mucosal adjuvant) by reducing the overall dose of CpG ODNs. Further, the biodegradable and essentially non-antigenic nature of the liposomes makes it superior than the other existing mucosal adjuvants.